PERENCANAAN BISNIS SULAM ALIS “FEELTHEBROWS” - Priscilla Pasaribu; Christiana Fara Dharmastuti (Prosiding Working Papers Series In Management, 2018)
Sulam alis “feelthebrows” is a business that do an eyebrow embroidery and located at East Jakarta. Feelthebrows is offering a service for eyebrow embroidery to fulfill what people need especially woman who wants to look more beautiful and appealing. Feelthebrows offer three variant of eyebrow embroidery, there are microblading, misty powder, and micropowder. The calculations NPV of this business for five years is Rp 2.305.694.328 and the result is positive, so its worth it to run this business. Keywords : eyebrow embroidery, service, woman